(untitled) (International journal of medical sciences, 2025)
The role of computer technology in medicine, as in other areas is incomparable. The use of computer technology in medicine has led to the improvement of digitization by a number of people to relieve fists. Improvements in performance and quality can be achieved. The quality of medical care, the general standard of living of the population, the level of development of the entire country and, in particular, each of its territorial entities depends on how effectively doctors, leaders, governing bodies use this information. Therefore, there is a need to use a large amount of information, and at the same time growing, in solving diagnostic, therapeutic, preventive and therapeutic problems. Statistical, management and other tasks, which today determine the creation of Information Systems in medical organizations.